TEACHER OF HIGHER VOCATIONAL SCHOOL AS A BASIS OF EDUCATION QUALITY - Bondarenko, V.; Kopytkov, D.; Бондаренко, В. В.; Копитков, Д. М.; Бондаренко, В. В.; Копытков, Д. М. (Харьковский национальный автомобильно-дорожный университет, 2017)
The personality of the higher vocational school teacher, the professional and pedagogical conditions to directly influence the educational process in the higher school, and the conditions for overcoming the contradictions that currently exist between the higher education, production and labor market have been considered.
ПЕДАГОГ ВИЩОЇ ПРОФЕСІЙНОЇ ШКОЛИ ЯК ОСНОВА ЯКОСТІ ОСВІТИ
ПЕДАГОГ ВЫСШЕЙ ПРОФЕССИОНАЛЬНОЙ ШКОЛЫ КАК ОСНОВА КАЧЕСТВА ОБРАЗОВАНИЯ
Keywords: motivation; professional education; higher education quality; teacher’s professional characteristics; мотивація; професійна освіта; якість вищої освіти; професійні характеристики педагога; мотивация; профессиональное образование; качество высшего образования; профессиональные характеристики педагога; 378:37.011